Pengembangan Pariwisata dalam Perspektif Community Based Tourism (CBT) di Wisata Wana Mukti Siguede - Nugraha, Joko Tri; Hidayat, Yudistira Wahyu; Mulyani, Sri; Sanjaya, Natta (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to analyze the development of community-based tourism or Community Based Tourism (CBT) in the Wana Mukti Siguede tourist attraction, Kebonlegi Village, Kaliangkrik District, Magelang Regency. The CBT concept was chosen because of the emphasis on active participation of local communities as the main actors in planning, management, and decision-making in the tourism sector. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the management of Wana Mukti Siguede tourism has implemented the five main dimensions in the CBT theory according to Suansri, namely economic, social, cultural, environmental, and political dimensions. This community-based management has been proven to provide a significant contribution to increasing income, preserving local culture, and strengthening community capacity. However, there are still challenges in its implementation, such as limited participation of the younger generation, environmental carrying capacity being exceeded, and the absence of formal regulations that comprehensively regulate resource management. Therefore, a strategy for strengthening capacity, improving management, and developing local regulations is needed so that tourism management can run optimally, sustainably, and fairly for the community. This research is expected to be a reference in the development of community-based tourism in other areas that have similar potential.